You Won’t Break My Soul: Black Women’s Pursuit of Joy in the Face of Racialized Police and Vigilante Violence - Sanders, Kaelyn (Journal of contemporary criminal justice, 2025)
Historically and presently, police and vigilante violence have been used as a racial control mechanism against Black people. As a result, Black people have more concerns about being mistreated because of their racial identity and being “Black in White space.” However, Black people’s traumas and anxieties are simultaneously experienced with positive emotions like joy, which can be used as a tool for resistance and healing from racial trauma. Notably, our current understanding of how free Black individuals feel to pursue joy, given the current social context, remains less understood. Understanding how freely Black people feel to pursue joy is important because it provides greater insight into their lived experiences in a hyper-policed and hyper-surveilled world and addresses calls to conduct scholarship that explores the entire “emotional gamut” of racial domination. Thus, this study uses data from interviews with 14 Black women who were engaged in activism to inductively assess if they feel free to pursue joy, given the police and vigilante violence Black people face. Findings suggest that the majority of participants felt that they were able to completely or conditionally pursue joy, which they described in a myriad of ways.